1998
DOI: 10.3168/jds.s0022-0302(98)75764-9
|View full text |Cite
|
Sign up to set email alerts
|

Management Practices Associated with Low, Medium, and High Somatic Cell Counts in Bulk Milk

Abstract: Management practices associated with bulk milk somatic cell counts (SCC) were studied for 201 dairy herds grouped into three categories according to bulk milk SCC. The cumulative production of fat-corrected milk over 305 d of lactation and category for bulk milk SCC were highly correlated; herds within the low category had the highest milk production. Differences in bulk milk SCC among the categories were well explained by the management practices studied. This correlation was not only true for the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
166
2
12

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(195 citation statements)
references
References 24 publications
14
166
2
12
Order By: Relevance
“…This was expected given the numerous previous studies that demonstrated the beneficial impact of post-milking teat disinfection on clinical and subclinical mastitis (Barkema et al, 1998). But, the practice was also associated with MAM through its link with the variable 'treatment for subclinical case'.…”
Section: Discussionmentioning
confidence: 87%
“…This was expected given the numerous previous studies that demonstrated the beneficial impact of post-milking teat disinfection on clinical and subclinical mastitis (Barkema et al, 1998). But, the practice was also associated with MAM through its link with the variable 'treatment for subclinical case'.…”
Section: Discussionmentioning
confidence: 87%
“…This analysis has particular significance because postmilking teat disinfection is a commonly used method. Barkema et al [21] observed that approximately 60 % of Dutch dairy farms were practicing postmilking teat disinfection. Evidence already exists that casts doubt on the efficacy of postmilking teat disinfection in the prevention of Escherichia coli (a colifom, major pathogen) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown an impact of mastitis control programs in reduction of the prevalence and incidence of mastitis (Barkema et al 1998b;Neave et al 1969;Hillerton et al 1993;Hillerton et al 1995;Zadoks et al 2002). Success is particularly easy to achieve in the case of S. agalactiae mastitis (Loeffler et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, practized on only 75% of dairy farms in Canada (Olde Riekerink et al 2006). Implementation of blanket dry cow treatment is less common in herds with a high BMSCC than in herds without a BMSCC problem (Barkema et al 1998b;Olde Riekerink et al 2006). To decrease the risk for new IMI with environmental pathogens during dry period, the longacting antibiotics might be combined with an internal wax sealant to prevent new IMI (Halasa et al 2010).…”
Section: Dry Cow Therapymentioning
confidence: 99%
See 1 more Smart Citation